Influence of urban catchment characteristics and rainfall origins on the phenomenon of stormwater flooding: Case study. (April 2022) - Szeląg, Bartosz; Suligowski, Roman; De Paola, Francesco; Siwicki, Piotr; Majerek, Dariusz; Łagód, Grzegorz
Abstract: This work presents a methodology for analyzing the influence of urbanization in a long-term approach on the number of floods in an urban catchment. The mathematical model presented for predicting the multiannual number of stormwater floods accounts for dynamic changes in the urban catchment in the subsequent years covered by the simulations. Logistic regression was applied to predict flooding occurring during rainfall events. The model may be applied to catchments with different characteristics. The assumed solution allows the development of early warning systems by modeling the occurrence of stormwater flooding in a studied catchment area based on the identification of the rainfall origin. To verify the simulations with a mathematical model, an innovative concept based on a hydrodynamic model is used; this concept includes the changes in the impervious area that occur during the simulation period. Highlights: Universal model to identify stormwater flooding in an urban catchment. Simulation of the influence of rainfall origins on stormwater flooding. Predict of the number of flooding considering the dynamics of land use changes.